2008
DOI: 10.1371/journal.pbio.0060142
|View full text |Cite
|
Sign up to set email alerts
|

Hox Paralog Group 2 Genes Control the Migration of Mouse Pontine Neurons through Slit-Robo Signaling

Abstract: The pontine neurons (PN) represent a major source of mossy fiber projections to the cerebellum. During mouse hindbrain development, PN migrate tangentially and sequentially along both the anteroposterior (AP) and dorsoventral (DV) axes. Unlike DV migration, which is controlled by the Netrin-1/Dcc attractive pathway, little is known about the molecular mechanisms guiding PN migration along the AP axis. Here, we show that Hoxa2 and Hoxb2 are required both intrinsically and extrinsically to maintain normal AP mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
131
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(138 citation statements)
references
References 81 publications
4
131
0
3
Order By: Relevance
“…So far, there is no direct evidence to support this possibility. However, many studies have indicated that Hox genes (mostly from cluster A) control cell adhesion and migration in hematopoietic cells (Leroy et al, 2004), epithelial cells (Mace et al, 2005;Arderiu et al, 2007) and pontine neurons (Geisen et al, 2008). If Hox expression patterns define the cell positional identity and behavior, how menin-MLL or RA-Fgf-Wnt signaling manipulate Hox networks and how Hox networks regulate cell-cell and cell-extracellular matrix interactions?…”
Section: Discussionmentioning
confidence: 99%
“…So far, there is no direct evidence to support this possibility. However, many studies have indicated that Hox genes (mostly from cluster A) control cell adhesion and migration in hematopoietic cells (Leroy et al, 2004), epithelial cells (Mace et al, 2005;Arderiu et al, 2007) and pontine neurons (Geisen et al, 2008). If Hox expression patterns define the cell positional identity and behavior, how menin-MLL or RA-Fgf-Wnt signaling manipulate Hox networks and how Hox networks regulate cell-cell and cell-extracellular matrix interactions?…”
Section: Discussionmentioning
confidence: 99%
“…Hence, other transcription factors should cooperate with Lim-HD proteins in patterning their growth. Hox code was shown to control axonal pathfinding in the spinal cord and hindbrain (Dasen et al, 2005;Geisen et al, 2008;Narita and Rijli, 2009;Watari-Goshima and Chisaka, 2011). It is possible that the diverse dA1 axonal tracts relay on different Hox genes.…”
Section: Possible Cues That Regulate Da1-axonal Projection Patternsmentioning
confidence: 99%
“…Thus, the different turning points of dA1 r6 -7 and dA1 r2-5 might be determined by Eph/Ephrin cues. Interestingly, the expression of these guiding cues is regulated by Hox, Lim-HD, and Zic genes (García-Frigola et al, 2008;Geisen et al, 2008;Wilson et al, 2008). Thus, elucidating the network between the transcriptional codes and the guiding cues in governing dA1 axonal trajectories is the focus of future studies.…”
Section: Possible Cues That Regulate Da1-axonal Projection Patternsmentioning
confidence: 99%
“…2D). Migrating precerebellar neurons express all Robo receptors (except Robo4) (Marillat et al, 2002;Marillat et al, 2004;Geisen et al, 2008). Slits are expressed in the floor plate, the rhombic lip and in several cranial motor nuclei, such as the facial nucleus (Geisen et al, 2008;Gilthorpe et al, 2002;Hammond et al, 2005).…”
mentioning
confidence: 99%
“…Interestingly, the migration of PN neurons is also perturbed in these mutants but in a different way. Upon leaving the rhombic lip, PN neurons migrate rostrally across several rhombomeres in a compact stream before turning ventrally towards the midline (Geisen et al, 2008). In Robo1/Robo2 and Slit1/Slit2 double knockouts, the stream of PN neurons splits and many neurons prematurely migrate towards the floor plate (Geisen et al, 2008).…”
mentioning
confidence: 99%